Acanthamoeba meningoencephalitis with hydrocephalus in an immunocompetent patient: A case report - Singh, Rahul; Sahu, Anurag; Singh, Kulwant; Prasad, Ravi Shankar; Pandey, Nityanand (Indian Journal of Case Reports, 2020)
Acanthamoeba is an unusual cause of meningoencephalitis having high mortality and it usually affects immunocompromised patients. We present a case of cerebrospinal fluid proven Acanthamoeba meningoencephalitis in a young male without immunosuppression. The patient presented with a chief complaint of fever for 1 month duration with features of meningoencephalitis, which progressed to rapid deterioration, and development of features of raised intracranial pressure. His initial contrast-enhanced computed tomography brain was normal but later on, magnetic resonance imaging of the brain showed features of hydrocephalus. Ventriculoperitoneal shunting was done followed by chemotherapy for Acanthamoeba and the patient recovered from illness.